Effect of change in temperature on the tribological performance of micro surface textured DLC coating - Arslan, A.; Masjuki, Haji Hassan; Varman, M.; Kalam, M.A.; Quazi, M.M.; Mosarof, M.H. (Materials Research Society, 2016)
In this study, surface texturing and hydrogenated amorphous carbon (a-C:H) diamond-like carbon (DLC) coating was combined to evaluate the coating performance at various temperatures in oil lubricated reciprocating sliding tests. Micro dimples were created by laser surface texturing on M2 steel using a Pico second laser. DLC coating was deposited by hybrid magnetron sputtering on textured substrates. Textured a-C:H showed stable coefficient of friction at 30, 80, and 125 °C compared to un-textured a-C:H. At 30 °C, graphitization was not observed for both textured and un-textured DLC coating. Graphitization was more pronounced in the case of un-textured a-C:H at 80 and 125 °C. Results show that, at all temperatures tested (30-125 °C), DLC textured samples showed higher wear resistance compared to un-textured DLC coating. The improvement in wear resistance can be explained by the lower graphitization of textured DLC coating. Lower graphitization in the case of textured DLC might be due to the wear particle capturing and lubricant retention ability of textures.